Activity corridors as an effective basis for the economic development and improvement of the standard of living of low-income communities - Lotz, Anton(Anton Petrus) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1995.